Mechanisms and Clinical Application Prospects of Curcumin in the Treatment of Sepsis - Zhang W; Liu S; Ma W; Huang D; Li Y (Journal of Inflammation Research, 2025)
Weidong Zhang, Siting Liu, Wangzhi Ma, Die Huang, Yongning Li Department of Emergency, The First Affiliated Hospital of Dalian Medical University, Dalian City, Liaoning Province, People’s Republic of ChinaCorrespondence: Yongning Li, Email lyn1009@126.comAbstract: Sepsis is a systemic inflammatory response syndrome caused by pathogenic microorganisms such as bacteria, fungi, viruses, and parasites invading the body. It is primarily characterized by an immune dysregulation in response to infection, leading to severe complications such as dysfunction of vital organs, shock, and disseminated intravascular coagulation (DIC), thereby threatening the patient’s life. Additionally, approximately 3 million surviving patients suffer from cognitive impairment, severely affecting their quality of life. Curcumin, a monomer of traditional Chinese medicine, has extensive pharmacological activity. Numerous studies have shown that curcumin can counteract the inflammatory response in sepsis and protect against organ damage caused by sepsis, suggesting that curcumin may become a new direction for sepsis treatment. In this review, we summarize the therapeutic effects and detailed mechanisms of curcumin in the treatment of sepsis based on current research.Keywords: sepsis, curcumin, inflammation, pyroptosis, oxidative stress